Dual courses of study from the perspective of the enterprises - a practical model of success through selection of the best provision available - Kupfer, Franziska [Verfasser] (My University, 2013)
"With the dual courses of study, a promising training model has taken root at the interface between vocational and university education. The number of courses offered by the universities and the demand on the part of enterprises and students has increased steadily in recent years. There are hardly any larger enterprises not offering dual study places. But why is it that companies engage in dual courses of study and what makes this study model so successful? In November 2012, the BIBB conducted an online survey among 280 enterprises that were participating in dual courses of study at universities of applied sciences. The results presented in this article show that dual courses of study are attractive recruiting tools for the enterprises although their quality potential may not yet have been exhausted." (author's abtract; BIBB-Doku)
Duale Studiengänge aus Sicht der Betriebe - Praxisnahes Erfolgsmodell durch Bestenauslese
Keywords: S 1.4.1 Ausbildung an Fachhochschulen; S 3.2 Unternehmen und Behörden; T 3.4 Befragung; Dualer Studiengang; Fachhochschule; Attraktivität; Betriebsbefragung